PEMANFAATAN ARTIFICIAL INTELLIGENCE UNTUK MENINGKATKAN EFISIENSI PEMBELAJARAN AL QURAN - Sukmawati, Anis (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2024)
Learning the Quran is an integral part of religious education. However, challenges in efficiency often arise in the learning process. The integration of artificial intelligence (AI) is expected to accelerate the learning and understanding of the Quran. On the other hand, it is important to recognize that excessive dependence on AI may potentially hinder human cognitive development. Therefore, a wise and cautious approach is necessary when utilizing AI. This research, through library research, aims to provide insights into ways to enhance the efficiency of Quranic learning by integrating AI into the learning process. The study considers the ethical and practical implications of using AI technology in religious education and evaluates its impact on the efficiency and effectiveness of Quranic learning. Additionally, this research identifies various opportunities and challenges in the utilization of AI. The findings indicate that integrating AI into Quranic learning not only improves the efficiency and effectiveness of the learning process but also opens up new opportunities. The results of this research are expected to encourage broader adoption of AI technology within the educational system, particularly in the context of religious education. By strengthening the understanding of how best to utilize AI technology in Quranic learning, it is hoped that more effective and holistic approaches can be developed. These approaches will combine the advantages of technology with the spiritual needs and meaningfulness inherent in learning the Quran.